Parent-School Cooperation as a Gender Sensitive Practice - Polovina, Nada (International Journal about Parents in Education, 2023)
This article explores the thesis that parent-school cooperation is predominantly a domain of female engagement. Our considerations are based on the analysis of gender related data accumulated during two national survey studies and five research projects focused on different aspects of parent-school cooperation (carried out between 2006 and 2010). The results of the analysed studies show that women make up 68% of the workforce in the education sector, and that women in Serbia spend on average 5 hours per day doing domestic work and 3 hours looking after children. In the five analysed research projects women are the dominant participants – out of 519 of the teacher participants in three studies 77% were women; out of 87 parent participants in three studies 81% were mothers. The results of the analysed research indicate that: mothers attend parent-teacher meetings seven to ten times during the school year, while fathers attend one to three times; cooperation with parents for teachers and cooperation with teachers for parents is not on the list of important everyday tasks; one important problem with regard to cooperation with parent is the impossibility of time alignment between parents and teachers. Possible strategies for enhancing family-school cooperation are also discussed.